Water wow! : an infographic exploration - Banyard, Antonia; Ayer, Paula (Annick Press, 2016)
An infographic introduction to the essential role water plays in everyday life combines text, photographs, and diagrams that cover such topics as climate change, the symbolism of water in religion, and conservation.